Dynamic testing of language learning aptitude: an exploratory proof of concept study - Du Fangfang; Beckmann Jens F. (Journal of China Computer-Assisted Language Learning)
This paper provides an example for how online technology can be utilised to increase efficiency and validity of assessment procedures beyond simple computerization of testing. We report the first steps of the development of an online assessment procedure for the measurement of language learning aptitude that is based on the concept of dynamic testing. Online adaptive dynamic tests provide learning opportunities in the test situation, allowing test takers demonstrate their ability to benefit from feedback. Test performance shown in such test procedures has been demonstrated to be more useful in predicting future learning and to represent a more valid indication of test takers’ learning potential. The newly developed online assessment procedure aims at measuring young learner’s ability to improve performance based on inductive reasoning across lexical, morphological and syntactic rules of an artificial language using pictorial stimuli. The test was administered on ten mainland Chinese children aged between 9 and 13. The tentative analysis indicates that the newly developed test is feasible and has the potential to be a useful diagnostic tool for measuring language learning aptitude. We report and discuss insights gained and outline how these will be utilised for the further refinement of this online assessment tool.